Context modulates evidence accumulation in split-second handball penalty decisions - Henrietta Weinberg; Florian Müller; Rouwen Cañal-Bruland (Cognitive Research)
Abstract Due to severe time constraints, goalkeepers regularly face the challenging task to make decisions within just a few hundred milliseconds. A key finding of anticipation research is that experts outperform novices by using advanced cues which can be derived from either kinematic or contextual information. Yet, how context modulates decision-making in split-second decisions remains to be determined. Here, we aimed at examining the influence of contextual information on real-time evidence accumulation in split-second decision-making using handball penalty decisions. In Exp. 1 we validated the applicability of hierarchical drift–diffusion modeling (HDDM) for the chosen split-second handball penalty scenario. Following validation, Exp. 2 directly addressed the main aim, namely, to examine how contextual information affects the HDDM parameters drift rate, as the rate of evidence accumulation, and non-decision time, which encompasses perceptual and motor processes. Participants predicted shot direction in temporally occluded videos of handball penalties, with probability (i.e., contextual) information regarding the shot direction being manipulated in half of the trials. Results showed that contextual information systematically affected the drift rate, indicating faster evidence accumulation when context information predicts the subsequent action. Vice versa, incongruent context information resulted in slower evidence accumulation. By contrast, non-decision time was only affected by the mere presence of contextual information (i.e., longer with context information). Our study is the first to show that contextual information modulates evidence accumulation on extremely short timescales in highly time-constrained penalty decisions.